Colonic endometriosis: First national observation - Cordero, Miguel; Toledo Correa, Nancy; Estapé, Gonzalo; Delgado, Bolívar (Cirugía del Uruguay, 1985)
C Description of a case of endometriosis of colon. lts endoscopic aspect adopts the form of an extrinsi• cal compression, with normal biopsy. lts treatment included viscera removal and removal of surrounding endomestriosic sources, with satisfactory evolution. Etiopathogenic, diagnostic and therapeutic consideration are done.